2017
DOI: 10.1097/mib.0000000000001251
|View full text |Cite
|
Sign up to set email alerts
|

Lasting Impact of Clostridium difficile Infection in Inflammatory Bowel Disease

Abstract: Background Inflammatory bowel disease (IBD) patients are at an increased risk of Clostridium difficile infection (CDI), but the impact of CDI on disease severity is unclear. The aim of this study was to determine the effect of CDI on long-term disease outcome in a matched cohort of IBD patients. Methods Patients who tested positive for infection formed the CDI positive group. We generated a 1:2 propensity matched case to control cohort based on risk factors of CDI in the year prior to infection. Healthcare u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…In a study from the University of Pittsburgh, it was shown that during the year of a C. difficile infection, having a C. difficile infection was significantly associated with more corticosteroid and antibiotic exposure and increased disease activity, worse quality of life and increased health care utilization (all P < 0.01) (38). During the next year after a C. difficile infection, patients continued to have increased exposure to C. difficile infection-targeted antibiotics ( P < 0.001) and other antibiotics ( P = 0.02).…”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%
“…In a study from the University of Pittsburgh, it was shown that during the year of a C. difficile infection, having a C. difficile infection was significantly associated with more corticosteroid and antibiotic exposure and increased disease activity, worse quality of life and increased health care utilization (all P < 0.01) (38). During the next year after a C. difficile infection, patients continued to have increased exposure to C. difficile infection-targeted antibiotics ( P < 0.001) and other antibiotics ( P = 0.02).…”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%
“…It has been reported that multiple cytokines and pro-inflammatory mediators from T cells and B cells, macrophages, synovial cells, as well as collagenases are involved in the initiation and development of the chronic inflammatory process in the RA synovial membrane (Granet and Miossec 2004). Synovial cells (macrophages and fibroblasts) present antigens to T cells, and then the activated T cells secrete multiple soluble mediators, including IL-1β and TNF-α (Anderson et al 2017). These mediators stimulate synovial hyperplasia and the production of collagenase and prostaglandin E2, which further aggravates the inflammatory response (Lin 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported in more severe pediatric IBD there exist dysbiosis of intestinal bacterial flora, which may have an impact on reducing resistance to colonization and hence increased susceptibility to CDI [37]. Even so, it is difficult to ascertain the relationship between disease activity in IBD and CDI; as CDI could in turn increase disease activity of IBD [38]. These findings suggested CDI and disease activity in IBD may be positively correlated.…”
Section: Discussionmentioning
confidence: 99%